Focus on further education of librarians in Latvia - Iveta Gudakovska (Information Research: An International Electronic Journal)
Describes the needs for continuing education of professional librarians in Latvia, following independence and the consequent structural changes. Following research into further education needs, the Continuing Education Centre for Librarians of Latvia (CECLL) was established to provide training courses. CECLL is a collaborative venture, involving the Department of Library Science and Information, University of Latvia, the Library Department of the National Library of Latvia and the initiative group of IT ALISE Ltd. The Centre is supported by funds from the Soros Foundation-Latvia and the Open Society Institute. The paper describes the courses offered, the further collaborative work of the Centre and the impact of its programmes.